2020
DOI: 10.1080/00049158.2020.1841440
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and heartwood variation of Santalum macgregorii in Papua New Guinea

Abstract: Santalum macgregorii (sandalwood), which is endemic to the southern part of Papua New Guinea (PNG), has been heavily exploited for its fragrant heartwood and is classified as threatened across its natural range. Domestication and smallholder agroforestry offer the means to preserve remaining diversity. This study was undertaken to understand the extent of remaining natural variation to support the species's conservation and domestication. We evaluated morphological, heartwood and essential oil characters in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Page et al (2010) identified subpopulation-level differences in %HW in a large sample of 264 S. austrocaledonicum trees growing in situ on seven island subpopulations in Vanuatu. Page, Jeffrey et al (2020) similarly found provenance variation in morphological, wood and oil characters among five provenances of S. macgregorii in Papua New Guinea. The differences in these studies may be attributable to subpopulation genetic variation, differences among the sites, or interaction between these.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Page et al (2010) identified subpopulation-level differences in %HW in a large sample of 264 S. austrocaledonicum trees growing in situ on seven island subpopulations in Vanuatu. Page, Jeffrey et al (2020) similarly found provenance variation in morphological, wood and oil characters among five provenances of S. macgregorii in Papua New Guinea. The differences in these studies may be attributable to subpopulation genetic variation, differences among the sites, or interaction between these.…”
Section: Discussionmentioning
confidence: 65%
“…A recent study of 126 Santalum macgregorii F. Muell. cores (Page, Jeffrey et al 2020), also using solvent extraction, found yields of less than 1% for all samples.…”
Section: Introductionmentioning
confidence: 89%
“…Heartwood percentage of Santalum macgregorii was 15.8%, with no significant differences between sites. A positive correlation was found between stem and heartwood diameter (Page et al 2020). The mean heartwood percentage of Indian sandalwood (S. album) trees at ground level (0 m) were 19.2%, and then continued to decrease up the tree to only 2.8% at 3.00 m (Jonathan et al 2012).…”
Section: Heartwood Content and Mai Of Heartwoodmentioning
confidence: 87%
“…The harvesting of S. macgregorii in PNG dates to the late nineteenth century and has continued intermittently ever since. In more recent decades, there have been reports of sporadic overharvesting (Paul 1990;Kiapranis 2006), leading to the species becoming rare in the wild (Page, Jeffrey et al 2020). Despite this, the trade in sandalwood continues today, with stands harvested in parts of Kairuku-Hiri District in Central Province and in Gulf Province due to increased accessibility from improved road networks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of oil properties in S. macgregorii have demonstrated remarkable variation between individual trees (Brophy et al 2009;Page, Jeffrey et al 2020). For the two most important fragrant compounds, α-and β-santalol, trees ranged from negligible amounts to very high levels that meet the international standard for Santalum album L. (ISO 2002).…”
Section: Introductionmentioning
confidence: 99%